Product Quality Evaluation of Smoked Catfish Producer in Pati Regency, Jawa Tengah based on Proximate, Microbiological, and Organoleptic Parameters - Tian Nur Ma'rifat; Erik Musafi'in; Hefti Salis Yufidasari; Bayu Kusuma; Angga Wira Perdana; Ahmad Syihab Fahmi Q.R.M.; Arief Rahmawan; Savaminee Teerawut (Journal of Agri-Food Science and Technology, 2026)
Smoked catfish is one of the popular fishery products in Indonesian society. Its soft meat and easy cultivation are the reasons why catfish is chosen as the raw material for making smoked fish. This research uses a case study of one of the smoked catfish producers (producer A) in Prawoto Village, Pati Regency, Central Java. The smoking process still uses traditional smoking. The research aims to determine the quality level of smoked catfish products from producer A and compare it to the quality level of benchmark product and the SNI standards. Quality analysis is carried out by chemical (protein, fat, moisture, and ash content), Total Plate Count (TPC) test, and organoleptic quality (the Rate-All-That-Apply (RATA) and hedonic tests). The results of the quality evaluation of producer A product:  protein content 25.21%, moisture content 55.57%, fat content 8.62%, ash content 1.39%, and for TPC was 3.7×103 CFU/g. Meanwhile, organoleptic tests on untrained consumer panelists showed that only a few parameters did not produce significantly different results. The quality parameters of product from producer A which have higher values compared to that from producer B are protein, moisture content, and TPC. When compared to the SNI standards, producer A, which is the main focus, has quality parameters that meet the requirements. Producer B, as a comparison, also meets the SNI standards. Recommendations to improve product quality include using a closed smoking process, and adding salt and liquid smoke for fresh catfish.